ANALISIS KOMUNIKASI VISUAL DALAM IKLAN PRODUK SKINTIFIC DI TIKTOK UNTUK MEMBANGUN DAYA TARIK KONSUMEN - gofur, fraya adinda; Fadillah, Dani (Borobudur Communication Review, 2026)
This study analyzes how visual communication in Skintific product advertisements on TikTok shapes consumer appeal and influences their perceptions and purchasing decisions. Using the approach of visual communication theory and message appeal, this study explores visual elements such as color, typography, animation, and visual narratives used in advertisements. Generation Z as the target audience shows a tendency towards creative and authentic visual content. The results of this study are expected to contribute to the development of more effective digital marketing strategies on short video-based social media such as TikTok.